Informal urban development in urban cities. Spatial assessment in the city of Batna, Algeria - Beddiaf, Walid; Dib, Belkacem (Technium Social Sciences Journal, 2022)
The development of the urban space of Algerian cities over the last thirty years has been characterized by an urban evolution that has been at odds with the various regulatory instruments of the state for shaping the urban space of cities, in particular, the land use plan (LUP), whose main objective was to guide, plan and control the urban development of urban space. However, the result today is the emergence of new fragmentary spaces that have informal forms and structures that break with the existing space. This type of informal trend is well-illustrated in the city of Batna and the region covered by land use plan No. 6. Therefore, the objective of this study is the evaluation of the urban development process of the area covered by the land use plan No. 06 by measuring the level of formality of that process from 2001 to 2018. The obtained results demonstrate that following the indicators selected, urban informality in the research region develops through time and space in a gradual and evolutionary form. The results obtained can be used as support for the development of a land use plan, if needed, but also for the implementation of a strategy to monitor the urban development of the city